Can Economic Growth, HDI, and Zis Contribute to Poverty Reduction In South Kalimantan? - Siti Madania; Zaki Mubarak (LPPM Universitas BSI, 2023)
This study investigates the impact of economic growth and the Human Development Index (HDI) on poverty, with Zakat Infaq Sedekah (ZIS) as a moderating variable. This study is quantitative, and the analytical methods consist of panel data regression analysis and Moderated Regression Analysis (MRA) aided by Eviews 9 data tools. The findings revealed that economic growth has a positive and substantial influence on poverty, whereas HDI has a negative and significant effect on poverty. However, ZIS does not mitigate the impact of economic development on poverty, nor does it modify the impact of the HDI on poverty. This result indicates that the ZIS does not help decrease poverty in South Kalimantan.Keyword: Economic growth, HDI, Poverty, ZIS